The Influence of Learning Methods and School Facilities on Student Learning Achievement - Yany, Muhammad; Syamsuria, Syamsuria; Faisah, Intan Nur; Andini, Andini (JUPE : Jurnal Pendidikan Mandala, 2023)
This research aims to determine the influence of learning methods and school facilities on the learning achievement of class XI MA Mattiro Deceng students, either partially or simultaneously. This research is quantitative research using the ex post facto method. The population in this study were all students in class XI MA Mattiro Deceng with a total of 12 students. Meanwhile, the sampling technique is full sampling. Data collection techniques are questionnaires and documentation. The data analysis technique used is multiple regression analysis. The research results show that variable XI and variable X2 simultaneously influence variable Y.